Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2014)
Welcome to Volume 16, Number 2 of Networks: An Online Journal for Teacher Research. I am happy to introduce you to another volume featuring the voices of educators. This issue includes articles that focus on talk in a grade three classroom, first year teachers in science classrooms, pre-service teacher development, action research in a special education classroom, dialogic interactions and reading, the project approach in kindergarten, as well as a short article on action research and first year faculty and a review of Critical Discourse Analysis in Education by Rebecca Rogers.